-45-4x=9x+8

Simple and best practice solution for -45-4x=9x+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -45-4x=9x+8 equation:


Simplifying
-45 + -4x = 9x + 8

Reorder the terms:
-45 + -4x = 8 + 9x

Solving
-45 + -4x = 8 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-45 + -4x + -9x = 8 + 9x + -9x

Combine like terms: -4x + -9x = -13x
-45 + -13x = 8 + 9x + -9x

Combine like terms: 9x + -9x = 0
-45 + -13x = 8 + 0
-45 + -13x = 8

Add '45' to each side of the equation.
-45 + 45 + -13x = 8 + 45

Combine like terms: -45 + 45 = 0
0 + -13x = 8 + 45
-13x = 8 + 45

Combine like terms: 8 + 45 = 53
-13x = 53

Divide each side by '-13'.
x = -4.076923077

Simplifying
x = -4.076923077

See similar equations:

| 5/x=18/5x+2 | | (3x-18)=195 | | 2x+2=8x-3 | | (3x-18)=180 | | 4x+9y=180 | | 9x-5=7x-1 | | Sin(x)=1.25287268 | | 4x-1=7x+20 | | y^2-225x^2=-9 | | 2x^2-80=x^2+6x+25 | | x^2+0.8x+0.1=0 | | 13x-1=2-2x | | -3x+8=2x-12 | | (x+3)(x-4)=(x-2)(x-1) | | f(x)=7-3x+6x^2 | | 12x-1=5-2x | | 12x-1=-2x+5 | | 2n=-2n+4 | | ln(5)=3x+4 | | 3x+5y-100xy=0 | | 16-25x^4=0 | | 4(3-2x)=9-(5+4x) | | 7x+7=6x+2 | | 5x+17=4x+9 | | 7a=5.3 | | 5g+2n+ry=r | | 5y-4x=-1 | | x^2-1000+60773=0 | | 15*x=76.50 | | 8x+3y=64 | | 22y+16x=2500 | | h(t)=16t^2+2304 |

Equations solver categories